Clinically important change on the Unified Dyskinesia Rating Scale among patients with Parkinson's disease experiencing dyskinesia - Pahwa, Rajesh; Fox, Susan; Hauser, Robert A.; Isaacson, Stuart; Lytle, Judy; Johnson, Reed; Llorens, Lily; Formella, Andrea E.; Tanner, Caroline M. (Frontiers in Neurology, 2022)
Background The Unified Dyskinesia Rating Scale evaluates dyskinesia in patients with Parkinson’s disease. The minimal clinically important change— smallest change in treatment outcome a patient considers important—remains undefined for Unified Dyskinesia Rating Scale. Objective Utilize pivotal amantadine delayed-release/extended-release (DR/ER) trial data to derive MCICs for UDysRS total score in patients with Parkinson’s disease experiencing dyskinesia. Methods Pivotal trials included Parkinson’s disease patients with ≥1 hour daily ON time with troublesome dyskinesia, and baseline scores ≥2 on the Movement Disorder Society-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) Part IV, item 4.2. Patients randomized to amantadine DR/ER or placebo completed 2 consecutive 24-hour diaries before each clinic visit and were evaluated during ON time with dyskinesia using Unified Dyskinesia Rating Scale, MDS-UPDRS, and Clinician Global Impression of Change. Unified Dyskinesia Rating Scale changes from baseline to Week 12 were anchored to corresponding changes in MDS-UPDRS item 4.2 scores. Minimal important improvement on Clinician Global Impression of Change and diary-reported ON time with troublesome dyskinesia (≥0.5 hours) were supportive anchors. Receiver operating characteristic curves determined Unified Dyskinesia Rating Scale change values optimizing sensitivity and specificity to ≥minimal improvement on each anchor. Results Analyses included 196 patients. Week 12 Unified Dyskinesia Rating Scale total score reduction ≥8 points corresponded to ≥minimal MDS-UPDRS item 4.2 improvement. Unified Dyskinesia Rating Scale reduction ≥9 points corresponded to decreased ON time with troublesome dyskinesia ≥0.5 hours per patient diaries, and Unified Dyskinesia Rating Scale reduction ≥10 points corresponded with at least minimal improvement on Clinician Global Impression of Change. Conclusions Anchored to MDS-UPDRS Part IV, item 4.2, an 8-point reduction in Unified Dyskinesia Rating Scale total score can be considered a minimal clinically important change for Parkinson’s disease patients with dyskinesia.